2006
DOI: 10.3800/pbr.1.155
|View full text |Cite
|
Sign up to set email alerts
|

Sand banks contribute to the production of coastal waters by making a habitat for benthic microalgae in the sublittoral zone: food web analyses in Aki-Nada using stable isotopes

Abstract: There are many sand banks in Seto Inland Sea, making patchy shallow zones less than 10 m deep. Due to the shallow environment, the surface sediment on the sand banks in the Hojo area, in the southern part of Aki Nada, Shikoku Island, Japan, often has a larger amount of benthic microalgae than other areas. We hypothesized that benthic microalgae contributed to the secondary production of coastal waters around sand bank areas, and investigated the food-web structure of the Hojo area using stable isotopes in earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
1
7
0
1
Order By: Relevance
“…The ratios of fish catch to primary production calculated for our study area were high compared to other studies such as 1.8% in the Seto Inland Sea (Uye et al 1987) and 1.2% in the North Sea (Steele 1974), although fish catch is not necessarily equal to fish production. In sublittoral areas, benthic algae attached on the sand banks have been suggested to contribute substantially to the production (Yoshino et al 2006). Stable isotope analyses by Yoshino et al (2006) suggested that fishes were sustained by benthic algae through polychaetes in the study area.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The ratios of fish catch to primary production calculated for our study area were high compared to other studies such as 1.8% in the Seto Inland Sea (Uye et al 1987) and 1.2% in the North Sea (Steele 1974), although fish catch is not necessarily equal to fish production. In sublittoral areas, benthic algae attached on the sand banks have been suggested to contribute substantially to the production (Yoshino et al 2006). Stable isotope analyses by Yoshino et al (2006) suggested that fishes were sustained by benthic algae through polychaetes in the study area.…”
Section: Discussionmentioning
confidence: 97%
“…In sublittoral areas, benthic algae attached on the sand banks have been suggested to contribute substantially to the production (Yoshino et al 2006). Stable isotope analyses by Yoshino et al (2006) suggested that fishes were sustained by benthic algae through polychaetes in the study area. Benthic algae were observed in the gut contents of many polychaete species in the Hojo area (Fukumoto 2000).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…O microfitobentos desempenha um importante papel na cadeia trófica, servindo como fonte alimentar para o meiobentos, foraminíferos e algívoros, formando assim uma das bases da teia alimentar, que alcança os níveis mais altos do macro e megabentos, como crustáceos e gastrópodes que pastejam e processam o sedimento epibentônico. Portanto, é necessário o conhecimento da distribuição microfitobentônica para entender melhor a distribuição dos taxa algívoros e demais níveis tróficos (Sundbäck & Person, 1981;Montagna, 1984;Santos et al, 1995;Miller et al, 1996;Macintyre et al, 1996;Gillespie et al, 2000;Pellizzari et al, 2005;Eichler et al, 2006;Yoshino et al, 2006;Netto et al, 2007;Ubertini et al, 2012).…”
Section: Introductionunclassified